Time-traveling through land and sea: unearthing the past to cultivate seeds of present and future solidarity. Issue 5 (28th May 2022) - Tachine, Amanda R.; Patel, Pooja R.; Daché, Amalia Z.
Abstract: In order to understand our present and future work in planting the seeds of solidarity, we excavate the past, through an exploration of transnational solidarity and the vestiges of U.S. legislative policy and philanthropy. Through life notes and sharing circles, we examine policies (Morrill Act of 1862, Refugee Act of 1980, and the Gates Millennium Scholars Program of 1999) that shaped our experiences as researchers, benefactors, and peoples of lands. Through a process of truth-telling and time traveling, we explore questions, tensions, and contradictions of our histories, our place in this world, and our interconnections with each other. We offer seeds that recognizes the juxtaposition of solidarity, a knowing of others' deep history, perplexing the abject and magical, and clairvoyance reflexivity. The work examines how we bond in difference and in the struggle, in qualitative research and in our lives.